Technical and managerial principles of a distributed cooperative development of a multi-lingual educational course - Bothe, K; Zdravkova, Katerina; Schuetzler, K; Budimac, Z; Bojic, D; Stoyanov, Stanimir (My University, 2003)
Seven universities of four countries are developing a joint course on software engineering which is web-based and has to cope with the challenges coming from different languages of the participating parties as well as with the distribution of work over the internet. This article describes the experience of this ongoing project in a generalized form to offer advice to similar forthcoming projects.